Pengaruh Religiusitas, Pengetahuan Dan Motif Rasional Terhadap Keputusan Mahasiswa Menabung Di Bank Syariah - dina fadilah; Nasution , Rizal Agus; Affandi , Ismi (Jurnal Bilal: Bisnis Ekonomi Halal, 2022)
This study aims to understand the influence of religiosity, knowledge, and rational motives on students' decisions to save at Islamic banks in the city of Medan. The study used a quantitative research approach, and data analysis was carried out using the multiple regression method. Data were collected through a survey by distributing questionnaires through an online form to 69 student respondents from the Medan State Polytechnic of Finance and Islamic Banking Study Program using a purposive sampling method. This study found that the variables of religiosity and knowledge partially had a significant effect on students' decisions to save at Islamic banks in the city of Medan, with significant values ​​of 0.000 and 0.009, respectively. And the rational motive variable partially has no significant effect on the student's decision to save at an Islamic bank in Medan, with a considerable value of 0.112. The variables of religiosity, knowledge, and rational motives simultaneously influence students' decisions to save in Islamic banks in the city of Medan. Because the F count is 78.730 > F table 2.75 (78.730 > 2.75) and the significant value obtained is 0.000 <0.05 (0.000 <0.05), the coefficient of determination test shows that religiosity, knowledge, and rational motives affect variation in the ups and downs of student saving decisions are as much as 77.3% while the remaining 22.7% is influenced by other variables not included in this study.   Penelitian ini tujuannya untuk mengerti pengaruh religiusitas, pengetahuan serta motif rasional pada keputusan mahasiswa menabung di bank syariah kota Medan. Penelitian memakai pendekatan kuantitatif riset dan analisis data dilaksanakan dengan metode regresi berganda, data dikumpulkan melalui survey dengan membagi kuesioner melalui online form kepada 69 responden mahasiswa Program Studi Keuangan dan Perbankan Syariah  Politeknik Negeri Medan dengan memakai metode sampel purposive sampling. Penelitian ini menemukan bahawa variabel religiusitas serta pengetahuan secara parsial berpengaruh signifikan terhadap keputusan mahasiswa menabung di bank syariah kota Medan dengan nilai signifikan masing masing sebanyak 0,000 dan 0,009. Dan variabel motif rasional secara parsial tidak berpengaruh signifikan terhadap keputusan mahasiswa menabung di bank syariah kota Medan dengan nilai signifikan 0,112. Variabel religiusitas, pengetahuan serta motif rasional secara simultan berpengaruh terhadap keputusan mahasiswa menabung di bank syariah kota Medan. Sebab F hitung 78,730 > F tabel 2,75 (78,730 > 2,75) dan nilai signifikan yang diperoleh sebanyak 0,000 < 0,05 (0,000 < 0,05),  uji koefisien determinasi memperlihatkan bahwa variabel religiusitas, pengetahuan dan motif rasional mempengaruhi variasi naik turunnya keputusan mahasiswa menabung ialah sebanyak 77,3% sedangkan sisanya sebanyak 22,7% dipengaruhi oleh variabel lainnya yang tidak termasuk pada penelitian ini.